PENGARUH WORKING CAPITAL TO TOTAL ASSET, OPERATING INCOME TO TOTAL LIABILITIES, TOTAL ASSET TURNOVER, RETURN ON ASSET, DAN RETURN ON EQUITY TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Teguh Erawati; Ignatius Joko Widayanto (Jurnal Akuntansi, 2016)
Capital market development in Indonesia is experiencing rapid growth. Capital markets provide attractive investment alternative for people or institutions that will invest. Investors are expected to benefit in the form of dividends and capital gains. This research wants to examine the effects of Working Capital to Total Asset (WCTA), Operating Income to Total Assets (OITL), Total Asset Turnover (TAT), Return On Asset (ROA) dan Return On Equity (ROE) to profit growth of manufacture company. The sampling technique used in this research is purposive sampling, with some criteria, those are: (a) the manufacture company listed in Indonesia Stock Exchange (IDX); (b) the manufactur company has positif profit in five consecutive years; (c) the avaliable of financial statement as the research 2010-2014 period. The result of this research shows that the data has fulfill the classical asumption, such as: no multicolinearity, no autocorrelation, no heteroscedasticity and distributed normally. From the regression analysis, found that partially Operating Income to Total Assets (OITL), Return On Asset (ROA), dan Return On Equity (ROE) variable, have a positive significant to profit growth of manufacture company, while Working Capital to Total Asset (WCTA) and Total Asset Turnover (TAT) doesn’t have influence to profit growth of manufacture company. From the research also known that those five variable (WCTA, OITL, TAT, ROA, and ROE) simoultaneously have an influence to profit growth of manufacture company. The prediction percentage of those variable simoultaneously are 27,8%. Keywords: WCTA, OITL, TAT, ROA, ROE, and growth.